Communication skills in primary care - Abdul Hadi, Azwanis; Azmi, Nurul Husna (IIUM Press, 2022)
Apart from solid medical knowledge, a primary care physician must be equipped with good communication skills. One of the main advantages of having good communication skills is to make it easier for the physician and patient to connect in order to reach holistic medical management. History taking is a structured medical interview comprising several important components that a physician must cover. History taking is usually the main platform that a physician uses to communicate with patients. When history taking is combined with verbal and non-verbal techniques, hopefully, successful communication between a physician